2002
DOI: 10.1037/0012-1649.38.4.543
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive profile and multiple-deficit hypothesis in Chinese developmental dyslexia.

Abstract: The present study was conducted to examine the cognitive profile and multiple-deficit hypothesis in Chinese developmental dyslexia. Thirty Chinese dyslexic children in Hong Kong were compared with 30 average readers of the same chronological age (CA controls) and 30 average readers of the same reading level (RL controls) in a number of rapid naming, visual, phonological, and orthographic tasks. Chinese dyslexic children performed significantly worse than the CA controls but similarly to the RL controls on most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
249
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(300 citation statements)
references
References 52 publications
41
249
1
5
Order By: Relevance
“…Given the clear differences in educational practices, language, and script between the two cultures included in the study, the consistency with which the Visual Spatial task was associated with Chinese character recognition across the groups was striking. A recent study on dyslexia in Hong Kong (Ho, Chan, Tsang, & Lee, 2002) also found that the task of Visual Spatial Relationships was particularly sensitive in revealing differences between 8-year-old dyslexic and normal readers. These results suggest that, regardless of age, the Visual Spatial Relationships task is a good predictor of reading skill in inexperienced Chinese readers, because dyslexic students typically have much less reading experience than do normal readers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the clear differences in educational practices, language, and script between the two cultures included in the study, the consistency with which the Visual Spatial task was associated with Chinese character recognition across the groups was striking. A recent study on dyslexia in Hong Kong (Ho, Chan, Tsang, & Lee, 2002) also found that the task of Visual Spatial Relationships was particularly sensitive in revealing differences between 8-year-old dyslexic and normal readers. These results suggest that, regardless of age, the Visual Spatial Relationships task is a good predictor of reading skill in inexperienced Chinese readers, because dyslexic students typically have much less reading experience than do normal readers.…”
Section: Discussionmentioning
confidence: 99%
“…Theory related to visual processing of text is relatively lacking for beginning readers. Based on the results of the present study and previous ones (Ho & Bryant, 1999;Ho et al, 2002;Siok & Fletcher, 2001), visual skills involving spatial relations, shape constancy, and visual memory may be the central ones to focus on in future research on beginning Chinese character acquisition.…”
Section: Critiques and Future Directionsmentioning
confidence: 96%
“…The most comprehensive study of dyslexia in Chinese to date was reported by Ho, Chan, Tsang, and Lee (2002), who classified data from 30 children with dyslexia on tests evaluating visual processing, phonological processing, and rapid naming, as well as on tests evaluating their knowledge of the orthographic regularities of characters and radicals. Results from this study indicate that a rapid naming deficit was the most dominant type of cognitive deficit in Chinese dyslexic children, affecting some 60% of the cases.…”
Section: Dyslexia In Different Languagesmentioning
confidence: 99%
“…Továbbá nem mehetünk el azon elméletek mellett sem, melyek a diszlexia több-komponensű természete mellett érvelnek (pl. Ho, Chan, Tsang és Lee, 2002;Wolf és Bowers, 1999).…”
Section: A Vizuális Kategorizáció Sérülése Patológiás Csoportbanunclassified